A DESCRIPTIVE ANALYSIS OF THE IMPACT OF DIGITAL TOOLS ON STUDENT ENGAGEMENT IN HIGHER EDUCATION - Sabri, Sabiroh Md; Ismail, Ismalaili; Annuar, Nursyamilah; Khushairi, Noor Azreen Mohd; Abdul Rahman, Normy Rafida (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
Student engagement plays a fundamental role in learning, directly influencing knowledge acquisition, skill development, and academic achievement. Research suggests that students who demonstrate high levels of engagement are more likely to participate in class discussions, collaborate effectively with peers, and take ownership of their learning journey. Engaged students also exhibit stronger problem-solving abilities and are more likely to retain and apply knowledge beyond the classroom setting. Despite the increasing adoption of digital tools in higher education, there remains a gap in understanding their direct impact on student engagement. While some studies highlight the benefits of technology-enhanced learning, others question its effectiveness in fostering meaningful engagement. This study aims to examine the impact of digital tools in promoting student engagement in university classrooms. A quantitative research approach was employed, utilizing survey data collected from 404 university students. Descriptive and frequency analysis were conducted using SPSS software to assess students’ perceptions of digital tools in their learning experiences. The findings indicate that digital tools positively influence engagement by enhancing interactivity, accessibility, and participation. However, challenges such as technological distractions and varying digital literacy levels were also identified. The results suggest that while digital tools can be effective in fostering student engagement, their implementation must be carefully structured to maximize benefits. The study provides insights for educators and policymakers on optimizing digital tool usage in higher education, ensuring a more interactive and engaging learning environment.